The BDNF val-66-met Polymorphism Affects Neuronal Morphology and Synaptic Transmission in Cultured Hippocampal Neurons from Rett Syndrome Mice - Xu, Xin; Garcia, Jordi; Ewalt, Rachel; Nason, Shelly; Pozzo-Miller, Lucas (Frontiers in Cellular Neuroscience, 2017)
Brain-derived neurotrophic factor (Bdnf) has been implicated in several neurological disorders including Rett syndrome (RTT), an X-linked neurodevelopmental disorder caused by loss-of-function mutations in the transcriptional modulator methyl-CpG-binding protein 2 (MECP2). The human BDNF gene has a single nucleotide polymorphism (SNP) – a methionine (met) substitution for valine (val) at codon 66 – that affects BDNF’s trafficking and activity-dependent release and results in cognitive dysfunction. Humans that are carriers of the met-BDNF allele have subclinical memory deficits and reduced hippocampal volume and activation. It is still unclear whether this BDNF SNP affects the clinical outcome of RTT individuals. To evaluate whether this BDNF SNP contributes to RTT pathophysiology, we examined the consequences of expression of either val-BDNF or met-BDNF on dendrite and dendritic spine morphology, and synaptic function in cultured hippocampal neurons from wildtype (WT) and Mecp2 knockout (KO) mice. Our findings revealed that met-BDNF does not increase dendritic growth and branching, dendritic spine density and individual spine volume, and the number of excitatory synapses in WT neurons, as val-BDNF does. Furthermore, met-BDNF reduces dendritic complexity, dendritic spine volume, and quantal excitatory synaptic transmission in Mecp2 KO neurons. These results suggest that the val-BDNF variant contributes to RTT pathophysiology, and that BDNF-based therapies should take into consideration the BDNF genotype of the RTT individuals.